Hydroxyapatite nanoparticles: an alternative to conventional phosphorus fertilizers in acidic culture media - Masumeh Noruzi; Parvin Hadian; Leila Soleimanpour; Leila Ma’mani; Karim Shahbazi (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Background Traditional phosphorus fertilizers generally have low efficiencies due to their immobilization in soil, and a large part of these fertilizers are not plant-available. Also, phosphorus resources are non-renewable. In recent years, a great deal of attention has been paid to nanofertilizers because of their slow or controlled release and also their very small particle size which increases the solubility and uptake of nanoparticles in plant. Hydroxyapatite nanoparticles are of great importance as phosphorus nanofertilizer thanks to their very low toxicity, biocompatibility, and the fact that products obtained from their degradation, i.e., phosphate and calcium ions, are naturally available in soils. Results In this study, hydroxyapatite nanoparticles were synthesized using the wet chemical precipitation method in three formulations and characterized with various techniques including electron microscopy, atomic force microscopy, X-ray diffraction, Fourier-transform infrared spectroscopy, and elemental analysis. Chemical and microscopic analyses showed that phosphorus was distributed in different parts of the wheat (Triticum aestivum L.) plant. To investigate the fertilizing effects of the nanoparticles, hydroxyapatite nanoparticles were used in different culture media including alkaline soil, acidic soil, the mixture of peat moss and perlite, and cocopeat. Based on our observations, hydroxyapatite nanoparticles showed fertilizing properties in all media. However, fertilizing potential strongly depended on the culture media. HAP nanoparticles demonstrated a high potential to be used as a fertilizer in acidic media. Nevertheless, only a slight fertilizing effect was observed in alkaline soils. Furthermore, the findings of our study showed fertilizing properties of powder hydroxyapatite nanoparticles without the need to convert them to suspension. Moreover, hydroxyapatite nanoparticles in all the three formulations showed low toxicity in such a way that their toxicity was even less than that of triple super phosphate. Conclusions Hydroxyapatite nanoparticles in both suspension and powder forms can be considered an alternative to conventional phosphorus fertilizers in acidic culture media. Our study revealed that hydroxyapatite nanoparticles were likely dissolved in the culture media and absorbed by plant mainly in the phosphate form. Graphical Abstract